Infections and antibiotic therapy in an Internal Medicine Service - Marques, Nuno (2005)
Introduction – Infectious pathology is one of the major causes of hospital admission in the Portuguese Medicine Services. Little data concerning the Portuguese reality is available and as such we are obliged at times to extrapolate from data of other countries.Objectives – To determine the characteristics of infectious pathology in a Portuguese Medicine Service.Methods – A 6-month prospective systematic study in a University Central Hospital Medicine Service was carried out. All patients diagnosed with an infectious pathology, either on admission or after bacteriologic or serologic studies, were included in the study. Results – 228 patients met the study inclusion criteria, 59% were female and the average age was 69.9 years. The most frequent infections were respectively: respiratory (83) and urinary (46). The most frequent cultural examinations required were blood culture for aerobes (194), urine cultures (187) and blood cultures for anaerobes (55). Percentage of positive identifi cation of infectious agents from cultural examinations was: blood cultures for aerobes 10.3%; urine cultures 25.7%; blood cultures for anaerobes 0% and sputum cultures 7.5%. In the 83 patients diagnosed with a respiratory infection, 4 agents were isolated and one serology were positive; the most frequent first line antibiotic therapy prescribed was amoxycillin + clavulanic acid. In the 46 patients diagnosed with urinary infection, 51 agents were isolated, 31 were community acquired infections and 20 nosocomial, predominantly Escherichia coli; the antibiotic sensitivity of the most frequent agents was determined; the most frequently prescribed fi rst line antibiotic therapy was: cephradine (34.4%), amoxycillin + clavulanic acid (31.2%) and ciprofl oxacin (21.9%). First line antibiotic therapy used was changed in 27.2% of cases, the chief reason for alteration was a weak clinical response.Discussion – The study sample refl ects the reality of infectious disease pathology in a Portuguese Medical Service. The cultural examinations were requested in accordance with the most frequent infectious diseases diagnosed. The profitability of the cultural examinations is the same as that found in international series, with the exception of low infectious agent isolation in sputum cultures and anaerobes in blood cultures. The low number of isolates in respiratory infections does not allow for conclusions to be drawn. The rate of isolated agents in community and nosocomial urinary infections is similar to that reported in international data. This study showed that nitrofurantoin and cephradine were the best antibiotic agents for community acquired urinary infections. The antibiotic therapy initially prescribed was sufficient in most cases and was altered in about 25% of cases. This small study represents some of the Portuguese reality and needs to be repeated, with a larger sample size, in order to draw firm conclusions and define the most adequate diagnostic and therapeutic guidelines for our reality.